Lung ventilation impairment in asthma patients with obesity - Feshchenko, Yu. I.; Gumeniuk, G.L.; Gumeniuk, M. I.; Zaikov, S. V.; Rekalova, O. M.; Opimakh, S. H. (Zaporozhye Medical Journal, 2019)
BA is characterized by more severe course, worse response to standard therapy in obese patients, therefore asthma with obesity is considered not just as comorbidity but as a distinct BA phenotype. Aim. To study the lung ventilation impairment in asthma patients with obesity using capnometry. The tasks are to study parameters of lung ventilation in asthma patients and healthy persons and to compare these parameters in asthma patients depending on the presence of obesity. Materials and methods. The study involved 60 participants (29 men and 31 women) aged 24 to 74 years, the mean age was 52.3 ± 2.7 years, including 30 patients with asthma and 30 healthy subjects. For all participants, body plethysmography and capnometry were performed. Results. The respiratory minute volume and alveolar ventilation volume were higher in asthma patients with obesity, and the volume of dead space ventilation and its fraction in the tidal volume were not substantially different among the groups of patients with BA. Specifically in relation to the gas exchange parameters, it was found that in obese asthmatics, the end-tidal carbon dioxide pressure was significantly increased – 4.8 ± 0.1 kPa compared with non-obese patients 4.3 ± 0.1 kPa, P < 0.05. The end-tidal oxygen concentration was significantly decreased – 15.3 ± 0.2 % compared to normal weight patients 16.0 ± 0.2 %, P < 0.05. Conclusions. Asthma patients with obesity have characteristics that include reduced total lung capacity, inspiratory capacity and forced vital capacity with a higher degree of airways obstruction. These changes lead to lung ventilation impairment with a tendency to carbon dioxide retention, which may be an unfavorable factor for the process of gas exchange with increased oxygen demands for the entire organism in obesity.